Factores biosociodemográficos y nivel de información del autocuidado en pacientes con diebetes mellitus tipo II, en emergencia - Vigo Valderrama, Martha Milagritos (2015)
The present study of investigation of descriptive, corelational type, of cross section, was realised in patients with mellitus diabetes, that entered to the Service of Emergencia of the Bethlehem de Trujillo; in order to demonstrate to the relation between biosociodemográficos Factors and the level of information of the self medication in these patients. The sample was constituted by 109 patients with diagnosis of mellitus diabetes type II, that fulfilled the inclusion criteria. For the data collection the instrument was applied: Scale of Evaluation of the Level of Information of Self medication by the Patient with Diabetes validated and reliable, applied Mellitus (EENIAPDM). The collected data were tabs, processings in SPSS version 15; appearing in tables of simple and double entrance, with numerical and percentage frequencies, as well as in graphs. Obtaining the following conclusions: within biosociodemográficos factors, we found that referring to the Age the 52,6 percent is adult majors; with respect to Sex the 65,5 percent is of feminine sex; in Index of Mass Corporal (I.M.C) the 50 percent has overweight; in the Level of training the 44,5 percent has a secondary level. Of the total of patients with mellitus diabetes type II, the 85,5 percent counts on a Level of regular information and the 8,5 percent has a level of high information. Statistical significance betweenb factors exists: Age and Level of training, with the level of information of the self medication in patients with mellitus diabetes type II (p < 0.05).